2003
DOI: 10.1002/ccd.10493
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on transradial approach vs. transfemoral approach in primary stent implantation for patients with acute myocardial infarction: Results of the test for myocardial infarction by prospective unicenter randomization for access sites (TEMPURA) trial

Abstract: Transradial coronary intervention (TRI) can be performed in elective patients with low incidence of access site complications. However, the feasibility of primary stent implantation by TRI is still not clear in patients with acute myocardial infarction (AMI). We prospectively randomized 149 patients out of 213 patients with AMI within 12 hr from onset into two groups: 77 patients treated by TRI (TRI group) and 72 patients by transfemoral coronary intervention (TFI; TFI group). We compared the incidences of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
65
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 25 publications
(30 reference statements)
8
65
0
5
Order By: Relevance
“…To the best of our knowledge, Saito et al 26 were the pioneers in comparing the safety and feasibility of the TRA and TFA approaches for patients with AMI undergoing primary PCI. Their results demonstrated that for selective patients with AMI, the TRA is comparable to the TFA in terms of the success rate of reperfusion and the incidence of in-hospital major adverse clinical events.…”
Section: Rationale Of Tra For Patients With Ami Undergoingmentioning
confidence: 99%
“…To the best of our knowledge, Saito et al 26 were the pioneers in comparing the safety and feasibility of the TRA and TFA approaches for patients with AMI undergoing primary PCI. Their results demonstrated that for selective patients with AMI, the TRA is comparable to the TFA in terms of the success rate of reperfusion and the incidence of in-hospital major adverse clinical events.…”
Section: Rationale Of Tra For Patients With Ami Undergoingmentioning
confidence: 99%
“…Furthermore, the indications for TRA have expanded to include the pPCI and treatment of complex lesions, such as those occurring at bifurcations and those creating total occlusion [15][16][17]. The most frequent complication after TRA is RAO; its incidence of around 5% may be higher for smaller RADs [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials performed after 2000 do not advocate this point when procedural success is compared to those reported for transfemoral PCI studies, especially when dedicated radial materials are used (2,11,37,57 As with the femoral approach, the ideal sizing and shape of guiding catheters is still, and will stay a matter for debate.…”
Section: Difficult Cases By Transradial Approach and Limits Of The Tementioning
confidence: 99%